Comparative Proteomic Analysis of Adhesion/Invasion Related Proteins in Cronobacter sakazakii Based on Data-Independent Acquisition Coupled With LC-MS/MS - Li, Ping; Dong, Xuan; Wang, Xiao-yi; Du, Ting; Du, Xin-jun; Wang, Shuo (Frontiers in Microbiology, 2020)
Cronobacter sakazakii is foodborne pathogen that causes serious illnesses such as necrotizing enterocolitis, meningitis and septicemia in infants. However, the virulence determinants and mechanisms of pathogenicity of these species remain unclear. In this study, multilocus sequence typing (MLST) was performed on 34 C.sakazakii strains and 2 strains with the same sequence type (ST) but distinct adhesion/invasion capabilities were selected for identification of differentially expressed proteins using Data-Independent Acquisition DIA proteomic analysis. A total of 2203 proteins were identified and quantified. Among these proteins, 210 exhibited differential expression patterns with abundance ratios 3 or 0.33 and P values 0.05. Among these 210 proteins, 67 were expressed higher and 143 were expressed lower in C.sakazakii SAKA80220 (strongly adhesive/invasive strain) compared with C.sakazakii SAKA80221 (weakly adhesive/invasive strain). Based on a detailed analysis of the differentially expressed proteins, the highly expressed genes involved in flagellar assembly, lipopolysaccharide synthesis, LuxS/AI-2, energy metabolic pathways and iron-sulfur cluster may be associated with the adhesion/invasion capability of C.sakazakii. To verify the accuracy of the proteomic results, real-time qPCR was used to analyze the expression patterns of some genes at the transcriptional level, and consistent results were observed. This study, for the first time, used DIA proteomic to investigate potential adhesion/invasion related factors as a useful reference for further studies on the pathogenic mechanism of C.sakazakii.